Deskripsi Kecerdasan Emosi Anak Usia Dini Kelompok B - Nurhayati Tine; Nunung S. Jamin; Irnawati S. Rafiudin (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
Thed aim of this study is to understand the early childhood emotional intelligence in group B of Nurul Yaqin Kindergarten, District of Buol. The population consists of 1 teacher and 6 students of group B of Nurul Yaqin kindergarten. The data was collected using interview, observation, and documentation techniques, and analysed by Miles and Huberman analysis; reduction, display, verification, and conclusion drawings. Emotional intelligence contributes to how children manage and express their emotions that vary among one another. The findings of the study are that both parents and teachers teach the children on how to develop their emotions, and that their roles are significant to build children’s positive emotions, such as giving them opportunities to express their emotions, to be patient, and willing to share. The conclusion of this study is the emotional intelligence is needed for one to be successful in life, and parents and teacher have a significant role to build it.